(untitled) (Research, Society and Development, 2021)
The study aims to verify the behavior regarding the risks for accidents with sharps in undergraduate nursing students, from a public Higher Education Institution in the interior of Amazonas, Brazil. This research is quantitative, descriptive, cross-sectional, with the target audience of undergraduate nursing students at the Institute of Health and Biotechnology of the Federal University of Amazonas. The data collection was carried out by 2 previously trained interviewers, from July to August 2017. The sample consisted of 94 students, of which 62.8% were female, mean age 22.5 years , and 78.7% were single. It was found that the majority (89.7%) used Personal Protective Equipment in practical classes and the prevalence of 5 accidents with sharps. Additional research is suggested to investigate the actions taken in relation to accidents with sharps that reach this public.